Entrepreneurs’ Behavioral Approach and its Impact on Small and Medium Scale Industries - Bajpai, Ankita; Srivastava, Shalini (AMC Indian Journal of Entrepreneurship, 2019)
Entrepreneurship is an art of structuring, creating, and running a new venture, which is often initially a small business. Those who create these ventures are known as entrepreneurs. In India, entrepreneurship has often been analyzed in terms of certain skills. The purpose of this study was to identify underlying factors of entrepreneurial behavioral competency framework and to know the difference in behavioral competencies across different demographic variables. Further, the study sought to examine the impact of behavioral competency on small and medium scale enterprises. The results revealed that demographic factors like age, type of business, and years spent in a particular business made a difference, while educational background of entrepreneurs did not make any difference in behavioral competency. Further, multiple regression result revealed that there was an impact of behavioral competency of entrepreneurs on small and medium scale enterprises. Although various studies have been done previously using aforesaid variables, there is a lack of literature on collective study in small and medium scale industries in the Indian context. Some researchers found that this sort of study can be performed for further improvement in related research. Hence, we attempted to know about the significant difference of competencies across various groups which will be helpful for academicians, researchers, and stakeholders to formulate strategies for entrepreneurial success.